2017
DOI: 10.1186/s13048-017-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing miR-199a-3p by promoter methylation contributes to tumor aggressiveness and cisplatin resistance of ovarian cancer through promoting DDR1 expression

Abstract: BackgroundDiscoidin Domain Receptor 1 (DDR1) belongs to the family of collagen receptor tyrosine kinases that confers the progression of various cancers. Aberrant expression of DDR1 was detected in several human cancers including ovarian cancer, which had been shown to increase the migration and invasion of tumor cells. However, the precise mechanisms underlying the abnormal expression of DDR1 in ovarian cancer has not been well investigated in previous studies.ResultsIn this work, a negative correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…Furthermore, in wt-p53 containing cells, cyclooxygenase 2 is upregulated under genotoxic stress and DDR1 activated cyclooxygenase 2 expression by NFKB pathway, leading to the resistance of breast cancer cells to etoposide [54]. Several studies demonstrated that DDR1 expression at protein level promotes the resistance of tumor cells to chemotherapeutic drugs like etoposide in lymphoma [55, cisplastine in ovarian cancer [56] and gefitinib in glioblastoma cells (both at the protein but also at RNA level) [57]. However, molecular mechanisms by which DDR1 leads to chemotherapy resistance remain unknown.…”
Section: Ddr1mentioning
confidence: 99%
“…Furthermore, in wt-p53 containing cells, cyclooxygenase 2 is upregulated under genotoxic stress and DDR1 activated cyclooxygenase 2 expression by NFKB pathway, leading to the resistance of breast cancer cells to etoposide [54]. Several studies demonstrated that DDR1 expression at protein level promotes the resistance of tumor cells to chemotherapeutic drugs like etoposide in lymphoma [55, cisplastine in ovarian cancer [56] and gefitinib in glioblastoma cells (both at the protein but also at RNA level) [57]. However, molecular mechanisms by which DDR1 leads to chemotherapy resistance remain unknown.…”
Section: Ddr1mentioning
confidence: 99%
“…chen et al (14) demonstrated that the deregulation of miR-199a-3p expression in testicular germ cell tumors may be due to hypermethylation of its promoter. The similar phenomenon was also investigated in ovarian cancer (15). In addition, miR-199a-3p was identified to improve cisplatin sensitivity in cholangiocarcinoma cells or breast cancer cells (16,17).…”
Section: Introductionmentioning
confidence: 79%
“…Vispé et al 44 found that DNA methyltransferase family (DNMT1, DNMT3A, and DNMT3B) were the major protein that maintains DNA methylation in cells, and 5‐aza‐2′‐deoxycytidine could consume DNMT1, resulting in DNA demethylation, re‐expression of tumor suppressor genes and DNA damage. Deng et al 45 verified that knockdown of DNMT3A significantly attenuated the expression level of miR‐199a‐3p. Therefore, miR‐199a‐3p is at a low expression level in HCC cells which is related to the maintenance of DNA methylation by DNMT family.…”
Section: Discussionmentioning
confidence: 99%